Dengue Virus Glycosylation: What Do We Know? - Yap, Sally S. L.; Nguyen-Khuong, Terry; Rudd, Pauline M.; Alonso, Sylvie (Frontiers in Microbiology, 2017)
In many infectious diseases caused by either viruses or bacteria, pathogen glycoproteins play important roles during the infection cycle, ranging from entry to successful intracellular replication and host immune evasion. Dengue is no exception. Dengue virus glycoproteins, envelope protein (E) and non-structural protein 1 (NS1) are two popular sub-unit vaccine candidates. E protein on the virion surface is the major target of neutralizing antibodies. NS1 which is secreted during DENV infection has been shown to induce a variety of host responses through its binding to several host factors. However, despite their critical role in disease and protection, the glycosylated variants of these two proteins and their biological importance have remained understudied. In this review, we seek to provide a comprehensive summary of the current knowledge on protein glycosylation in DENV, and its role in virus biogenesis, host cell receptor interaction and disease pathogenesis.